Evaluation of different nutrient management practices for the Boro-T. aman rice cropping pattern in old Meghna estuarine flood plain (Bangladesh Journal of Agricultural Research, 2007)
Three field experiments were conducted during 2002 to 2004 at Multi Location Testing site, Feni to evaluate different nutrient management packages for the Boro-T. aman rice cropping pattern. Four nutrient management packages along with existing farmers' practice and no fertiiler were tested. Four fertilizer management packages were soil test based (STB) fertilizer dose for moderate and high yield goals (MYG and HYG), IPNS with cowding for HYG and AEZ basis fertilizer dose (FRG'97). Three years' average result showed that IPNS and STB (MYG) treatments gave significantly higher yield in both Boro and T.aman rice. For both rice crops, the yield contributing characters were correlated with the yield of rice The average gross margin was highest (Tk. 79964/ha) in IPNS, but the highest MBCR (6.48) over control was obtained with FRG'97 due to less fertilizer cost. Nutrient uptake and nutrient balance showed that the crops removed considerable amounts of N, P, and K every year. The N and K balances were negative in all cases. Bangladesh J. Agril. Res. 32(2) 2007: 291-299.